Synthesis and characterization of CeF3‒doped (74.5-x)P2O5:20Li2O:5Al2O3:x(GdF3, LaF3 and YF3) glasses. (December 2021) - Aryal, P.; Saha, S.; Kim, H.J.; Kang, S.J.; Ntarisa, A.V.; Angnanon, A.; Kaewkhao, J.
Abstract: Glasses have a wide variety of applications in different types of devices, including solid-state lasers, fiber-optic amplifiers, medical imaging, radiation dosimeter, solar cells, neutron imaging, and scintillators. Among several rare-earth (RE) ions, Ce 3+ exhibits short decay time and offers promising scintillation when it is doped in a transparent glass matrix. The objective of this study was to investigate the energy transfer from Gd 3+, La 3+, and Y 3+ ions to Ce 3+ ion in 64.5P2 O5 :20Li2 O:5Al2 O3 glass matrix while considering an enhancement in its scintillation efficiency. Four glass samples doped with CeF3 alone and co-doped with GdF3, LaF3, and YF3 were fabricated. Broad photoluminescence and radio-luminescence emissions peaking near to 340 and 350 nm were found when excited by 310 nm and X-ray, respectively, for all the glasses. A photoluminescence emission quenching was found in LaF3 co-doped glass. A strong energy transfer from Gd 3+ to Ce 3+ was noticed while the GdF3 co-doped glass was excited by X-ray, 275 nm (from Gd 3+ ), and 310 nm (from Ce 3+ ) excitations. The Gd 3+ co-doped glass consisted of a 37 ns decay constant under the 266 nm laser excitation. The thermoluminescence analysis showed two glow curves centered at 210 °C and 345 °C, respectively, after X-ray irradiation. Considering the efficient energy transfer from Gd 3+ to Ce 3+ ions and short lifetime of Ce 3+ emission, the glass composition of the above formula having Gd 3+ and Li + with Ce 3+ ions appeared to be a promising candidate in the search of good promising scintillating glasses with fast fluorescence decay time. Highlights: Ce 3+ activated lithium phosphate glasses doped with Gd 3+, La 3+ and Y 3+ were prepared. Photoluminescence, X-ray luminescence and thermoluminescence were analyzed. Gd 3+ transfers the highest energy to Ce 3+ among other co-doping. Ce 3+ and Gd 3+ co-doped glass matrix is appropriate to apply as glass scintillator.